دلالة النمط التركيبي والخصائص الموضوعية لسور ’’حم‘‘: Connotation of synthetic style and characteristics of Surahs - محمد ضیاء الله; ٔ.د.شفقت الله (JAR, 2023)
The language of the Quran is unsurpassed in its accuracy of meaning and expression. Each letter and word has its place while the language is errorless. Undoubtedly, it is the words of Almighty that is revealed to the Prophet Hazrat Muhammad PBUH and transmitted to us through an authentic and continuous narration. Many of surahs of the Holy Quran start with حم. These surahs have very special type of rhetoric and eloquence. The aim of this study is to highlight the synthetic style and characteristics of these surahs. The article applies the descriptive, qualitative and applied method for this research. The study found that these surahs have unique features with special reference to synthetic study. The study also found that inability to produce anything like the Holy Quran, due to its unique literary style, is the essence of the Quranic miracle. At the end of the study, the researchers have drawn various conclusions.